A Juridical Analysis of Intellectual Property Rights as Fiduciary Guarantees in Banking Institutions - Karim, Asma (IHSA Institute, 2024)
This study aims to find out and analyze the mechanism for assessing intellectual property rights as fiduciary guarantees in banking institutions and the mechanism for implementing the execution of intellectual property if the debtor defaults. The results showed that the mechanism for assessing intellectual property rights as fiduciary guarantees in banking institutions involves several requirements, namely: first, sub-mission of applications for intellectual trust-based financing to financial or banking in-stitutions by completing the following requirements: Financing proposals, having a creative economy business; Have an engagement related to creative economy IP; have a registration letter or IP certificate. Second: bank financial institutions or non-bank fi-nancial institutions in providing intellectual property-based financing carry out: verifi-cation of creative economy businesses; verification of registration letters or intellectual property certificates that are used as collateral that can be executed in the event of a dispute or non-dispute; valuation of intellectual property used as collateral; disburse-ment of funds to creative economy actors; and receipt of financing returns from Crea-tive Economy Actors in accordance with the agreement